Musicogenic epilepsy in paraneoplastic limbic encephalitis: a video‐EEG case report. Issue 5 (16th November 2021) - Morano, Alessandra; Orlando, Biagio; Fanella, Martina; Irelli, Emanuele Cerulli; Colonnese, Claudio; Quarato, Pierpaolo; Giallonardo, Anna Teresa; Di Bonaventura, Carlo
Abstract: Musicogenic epilepsy (ME), a peculiar form of reflex epilepsy, represents a neurological rarity and yet another demonstration of the extraordinary power of music on the human brain. Despite the heterogeneity of the reported musical triggers, patients' emotional response to music is thought to play a crucial role in provoking seizures. Accordingly, the mesial temporal structures (especially of the non‐dominant hemisphere) appear most involved in seizure generation, although a more complex fronto‐temporal epileptogenic network was documented in some cases. Autoimmune encephalitis has been recently included among the many possible aetiologies of ME based on a few reports of music‐induced seizures in patients with anti‐glutamic acid decarboxylase 65 antibodies. Here, we describe the case of a 25‐year‐old man, educated in music over a long period of time, who had suffered from drug‐resistant temporal lobe epilepsy following seronegative limbic encephalitis related to non‐Hodgkin lymphoma. Along with spontaneous events, the patient also developed musicogenic seizures later in the disease course. After detecting five music‐induced episodes via 24‐hour ambulatory EEG, we performed prolonged video‐EEG monitoring during which the patient presented a right temporal seizure (characterized by déjà‐vu, piloerection and gustatory hallucinations) while listening to a hard rock song through headphones (which he had not previously heard). This observation allowed us to confirm the provoking effect of the music on our patient's seizures, despite the lack of any emotional drive, which suggests that a "cognitive" trigger was more likely in this case. Our report further highlights that autoimmune encephalitis should be investigated as a novel potential cause of musicogenic epilepsy, regardless of autoantibody status.